HUBUNGAN BEBAN KERJA DENGAN STRESS KERJA PADA PERAWAT DI RUMAH SAKIT HJ BUNDA HALIMAH BATAM TAHUN 2024 - kasim, felix; ginting, selamat; Ardha, Frizchilya (Deli Medical and Health Science Journal, 2025)
The workload of nurses in hospitals is affected by the type of case severity, the degree of patient dependence and the number of cases. The higher standard of health services in the modern era has had an impact on increasing the psychological workload of medical personnel in hospitals. The Excessive psychological workload can result in stress, physical and psychological fatigue, and decreased performance and productivity.The type of the research used is quantitative research with a Cross-Sectional approach or research that aims to determine the relationship between workload and work stress in nurses at HJ Hospital Bunda Halimah Batam in 2024. The population in the research is all nurses at the HJ Hospital. Bunda Halimah Batam Hospital. The selection of samples in this study was carried out using the Slovin formula so that 38 respondents were obtained.Based on the results of statistical tests using chi-square, it was obtained that there was a workload relationship based on physical aspects with work stress obtained a p value of 0.027, then there was a relationship between workload based on psychological aspects with work stress obtained a p value of 0.046, and there was a workload relationship based on time aspects with work stress obtained a p value of 0.029. In the multivariate analysis, it was found that the physical aspect variable in the workload was the most influential variable in work stress 8,643 times Expected to HJ Hospital Bunda Halimah Batam to increase the number of nurses who are balanced with the number of patients entering or vice versa by increasing skills and responsibilities, it is hoped that with more skills, many tasks are not a burden for them.